The International Court of Justice, the Whales, and the Blurring of the Lines between Sources and Interpretation - d’Aspremont, Jean (European journal of international law, 2016)
Abstract In the contemporary mainstream configuration of most legal orders, a given norm or standard of behaviour is said to be binding upon legal relations between subjects if that norm or standard can be validated by virtue of the doctrine of sources of that legal order. In most legal orders, including international law, the doctrine of sources even enjoys a monopoly on the tracing of bindingness, bearing only remotely or indirectly upon the interpretation of the content of those standards and norms that sources recognize as valid. The idea that the doctrine of sources enjoys a monopoly on the tracing of bindingness and does not constrain interpretation has been seriously eroded by the International Court of Justice in its 31 March 2014 judgment concerning Whaling in the Antarctic. As will be explained in this article, the Court comes very close to calibrate the interpretive effects of the resolutions of the International Whaling Commission through the doctrine of sources. As will be shown, this blurring between sources and interpretation warrants the attention given the efforts that the Court had, over the years, invested in consolidating two distinct doctrines – that is, the doctrine of sources and the doctrine of interpretation. After briefly recalling how the relation between interpretation and sources was approached by the Court, a critical look is taken at the implications of the judgment from the vantage point of the distinction between bindingness and interpretive effects. This brief article ends with a few remarks on the oscillations between sources and interpretation witnessed in contemporary international legal discourses.